PRELIMINARY TESTING OF THE ECOLOGICAL INTERACTIONS BETWEEN PINES AND OAKS OF CONIFEROUS FORESTS OF DURANGO, MEXICO - Cháidez, José de Jesús Návar (Floresta, 2004)
In this paper it was tested the independence of diameter structures of oak and pines sharing resources in forest stands of the western Sierra Madre mountain range of Durango, Mexico with the aim to detect ecological interactions between these two genera. Regression analysis was conducted on the weibull distribution parameters fitted independently to diameter structures of pines and oaks. The moments methodology of parameter estimation of the Weibull distribution was fitted. This procedure was independently carried out for pine and oak diameter structures of mixed and uneven-aged forests. The regression analysis conducted on the weibull parameters for pines and oaks did not show patterns or tendencies with sufficient statistical meaning. Indeed the diameter structures of pines and oaks are quite similar and showed little sensitivity to changes in the weibull parameters stressing the potential independence of diameter growth of pines and oaks. Further research is required to understand the ecological interactions between oaks and pines, at the species scale, with the aim to develop growth and yield models to sustainable manage the mixed, uneven-aged coniferous forests of Durango, Mexico. Resumen En este reporte se probó la independencia de las estructuras diamétricas de pinos y latifoliadas compartiendo los bosques de la Sierra Madre Occidental de Durango, México, con el objetivo de detectar relaciones ecologicas entre estos dos géneros. Se realizaron análisis de regresión entre los parámetros de la distribución weibull, ajustados independientemente a las estructuras diamétricas de pinos y latifoliadas. Se usó la metodología de momentos para estimar los parámetros de la distribución Weibull. Este procedimiento se realizó independientemente para las estructuras diamétricas de pinos y latifoliadas de los bosques mixtos e irregulares de Durango, México. Los análisis de regresión, realizados entre los parámetros de la distribución Weibull, no mostraron tendencias o patrones con significado estadístico suficiente. Las estructuras diamétricas de pinos y latifoliadas son muy similares y mostraron baja sensibilidad a los cambios en los parámetros de la distribución Weibull estresando la potencial independencia en el crecimiento diamétrico de pinos y latifoliadas. Se requiere investigación adicional para entender las interacciones ecológicas entre las latifoliadas y los pinos, a la escala de especie, con el objetivo de desarrollar modelos de rendimiento e incremento para manejar sosteniblemente los bosques mixtos e irregulares de coníferas de Durango, México.